Potential use of nuisance cyanobacteria as a source of anticancer agents - Lee, Hojun; Depuydt, Stephen; Choi, Soyeon; Kim, Geonhee; Kim, Youngdo; Pandey, Lalit K.; Häder, Donat-Peter; Han, Taejun; Park, Jihae (Natural Bioactive Compounds: Technological Advancements, 2020)
The undesirable accumulation of cyanobacterial biomass, “green algal bloom, " has deleterious effects on the ecological stability of water bodies. It is equally notable that the huge cyanobacterial biomass can be used in the production of valuable biocommodities, including biofuels, functional food ingredients, UV-absorbing compounds, and pharmaceutical products. Cyanobacteria are known as a rich source of biopigments, fibers, antioxidants, vitamins, polysaccharides, mycosporin-like amino acids, proteins, and essential lipids. This review provides a summary on the various bloom-forming cyanobacterial species and their metabolites as a promising source of anticancer agents.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Anticancer agents; Cyanobacteria; Green algal bloom; Metabolites